Enhancing Financial Reporting Quality in MSMEs: A Case Study of MYOB Accounting Implementation at Abadi Cell, Indonesia - Evelyn Felicia Setiawan; Tina Miniawati Barusman (PT. Altaf Publishing Corp, 2026)
This study aims to analyze the implementation of MYOB Accounting software in preparing financial reports at Abadi Cell MSME in East Lampung and to evaluate the quality of the financial statements based on Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The research uses a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation of financial data from the business. Before implementing MYOB, financial records were prepared manually using Microsoft Excel and sales notes, which resulted in incomplete and unsystematic financial reports. The results show that the use of MYOB improves the effectiveness and efficiency of financial transaction recording and produces more structured financial statements, including statement of financial position, income statement, and cash flow statement. The implementation of MYOB also reduces human error and enhances the transparency of financial information. Therefore, MYOB-based accounting implementation can support better financial management and managerial decision making for MSMEs.